2017
DOI: 10.1021/acs.iecr.7b04501
|View full text |Cite
|
Sign up to set email alerts
|

Copolymeric Schiff Base Cu: A Platform for Active and Recyclable Catalyst in Aerobic Oxidations

Abstract: The synthesis of heterogeneous metal–ligand catalysts with high activity and good recyclability is always an important topic but still challenging to make. Herein, we reported a solid Schiff base Cu catalyst synthesized by incorporating Cu sites into the copolymeric Schiff base ligand, which is achieved from a porous polydivinylbenzene functionalized with Schiff base groups. A heterogeneous Schiff base Cu catalyst denoted as hetero-SchCu was obtained. Systemic characterizations involving XPS, FTIR, N2 sorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…[6][7][8][9] However, they suffer from some disadvantages such as the problem of separation and recovery from the reaction mixture at the end of the process. 10 Hence, designing catalytic systems of Schiff base complexes with easy recyclability is still a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] However, they suffer from some disadvantages such as the problem of separation and recovery from the reaction mixture at the end of the process. 10 Hence, designing catalytic systems of Schiff base complexes with easy recyclability is still a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…[8] So, for improving the efficiency of their catalytic activity and ease of separation from reaction media, scientists have tried to convert them into heterogeneous systems in various ways. In this light, several methods can be used, such as: (1) linking onto metal oxides such as silica, Fe 3 O 4 and so on, [9][10][11] (2) immobilizing on organic supports like graphene oxide [12,13] and carbon nanotubes, [14] (3) copolymerizing and incorporating into an organic polymer like chitosan or porous polydivinylbenzene [15][16][17][18][19] and (4) encapsulating in various zeolites. [20][21][22] Organosulfur compounds such as sulfoxides and sulfones are very important compounds in organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The applications of Schiff bases have received ever-increasing attention because the characteristic chemical bond [−(CN)−] has excellent ion coordinative capability , and pH-responsive ability . Schiff bases and their derivatives have been widely used for developing catalyst intermediates, , biological sterilizations, , fluorescent reagents, , self-assembled polymers, , and polymer stabilizers . More recently, it was reported that Schiff bases can be used as electrodes for batteries and used to prepare metal–organic frameworks (MOFs) , and covalent organic frameworks (COFs) .…”
Section: Introductionmentioning
confidence: 99%
“…SCB(−) ] as an example, the release process was carried out in the mixed solution (volume ratio, water/ethanol = 1/9) because the citronellal is only slightly soluble in water. The release systems were recorded as solution (pH 1,3,5,7,11). By UV−vis spectra analysis, the results are shown in Figure4.…”
mentioning
confidence: 99%